2022
DOI: 10.1039/d2ta02340g
|View full text |Cite
|
Sign up to set email alerts
|

The peculiarities of charge distribution and spatiotemporal changes in electronic and atomic structure of bone tissue

Abstract: X-ray diffraction and inner-shell photoemission studies of rat cortical bone were performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Surface charge refers to the free charge accumulated at the interface of the material, which is divided into positive charge and negative charge. Previous studies have found that bones can be seen as composed of a large number of negatively charged nano-hydroxyapatite crystals and positively charged hydrated nano-layers [52]. The type and amount of charge on the surface of bone repair materials will affect the effect of bone repair.…”
Section: Surface Charge Affects Osteogenesis Through Protein Adsorpti...mentioning
confidence: 99%
“…Surface charge refers to the free charge accumulated at the interface of the material, which is divided into positive charge and negative charge. Previous studies have found that bones can be seen as composed of a large number of negatively charged nano-hydroxyapatite crystals and positively charged hydrated nano-layers [52]. The type and amount of charge on the surface of bone repair materials will affect the effect of bone repair.…”
Section: Surface Charge Affects Osteogenesis Through Protein Adsorpti...mentioning
confidence: 99%